Jacques Joseph: Father of modern aesthetic surgery - Bhattacharya Surajit (Indian Journal of Plastic Surgery)
When we review the history of modern aesthetic surgery, a name that stands out as bright as a beacon and precious as gold is undoubtedly that of Jacques Joseph. A surgeon, par excellence, far ahead of his time, who chose to think out of the box, Joseph, despite all odds set out to give respectability to Aesthetic Surgery without depriving it of any scientific core values. By his words and deeds proved beyond doubt that only the very best in the field of reconstructive surgery, can visualize the hidden perfection in imperfection and formulate a treatment plan and a surgical strategy to achieve that elusive perfection. The rich surgical literature that he has left behind, the wealth of surgical instruments that he had designed and above all a way of thinking that he propagated, that aesthetic surgery is not frivolous but very serious endeavor, and treating the psychology of the patient is as important as treating his disease, undoubtedly makes him the revered ′Father of Modern Aesthetic Surgery′.